Hemoglobin-to-Red-Cell Distribution Width Ratio Is a Novel Predictor of Long-Term Patient Outcomes After Percutaneous Coronary Intervention: A Retrospective Cohort Study - Xiu, Wen-Juan; Zheng, Ying-Ying; Wu, Ting-Ting; Hou, Xian-Geng; Yang, Yi; Ma, Yi-Tong; Xie, Xiang (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The hemoglobin level and red cell distribution width (RDW) have been linked to the prognosis of coronary atherosclerotic heart disease (CAHD). However, the relationship between the ratio of hemoglobin to the RDW (HRR) and clinical outcomes after percutaneous coronary intervention (PCI) is not known. Here, we explored the impact of the HRR on clinical outcomes after PCI. Methods: In our study, we selected 6046 CAHD patients with PCI hospitalized in the First Affiliated Hospital of Xinjiang Medical University from 2008 to 2016. The patients were grouped according to their HRR ratio: group A (HRR < 10.25, n=2344) and group B (HRR ≥ 10.25, n=3702). The difference in clinical outcomes between the two groups was compared. Patients were followed up for 35.9 ± 22.6 months. Results: Three hundred nine patients died during follow-up. These included 166 patients (7.1%) in the HRR < 10.25 group and 143 patients (3.9%) in the HRR ≥ 10.25 group (P<0.001). The incidences of cardiogenic death (5.7% vs. 3.2%) and major cardiovascular adverse events (16.5% vs. 12.9%) also differed significantly between the groups (both Ps < 0.001). Analysis using the multivariate Cox proportional hazard model found a significant association between a decreased HRR and post-PCI mortality (all-cause death, adjusted HR: 1.479, 95% CI: 1.156-1.893, p=0.002; cardiac death, adjusted HR: 1.470, 95% CI: 1.116-1.936, p=0.006). Conclusion: The HRR is predictive of post-PCI mortality among CAHD patients.